Identities, issues, and interactions in Southeast Asian facebook groups and its effects - Uyseco, Wayne Winter J.; Uyseco, Wayne Winter J.; Santarita, Joefe B. (Quezon City Asian Center, University of the Philippines Diliman, 2019)
"The study focuses on the identity, issues, and interactions of Southeast Asians in the Facebook groups "We are ASEAN" (WAA) and "Southeast Asia 360 (SEA360) and its effects. The study utilized an online survey administered to 65 WAA and 30 SEA360 members. Observations were also made by the researcher from 2015 to 2018 and an interview of an expert was also conducted in this exploratory study. Results show that individuals present themselves in varied ways, identifying oneself as a national of a certain country in posts that promote the country against other countries or identifying oneself as part of an ethnic group in posts that discuss similarities and differences in a certain country. Few respondents mentioned that they are Southeast Asians in the said groups. The analysis also shows that members positively interact with one another in posts related to physical environment and some current events, while some negatively interact with one another in posts related to socio-economc development, culture, and other current events. The survey data also show that respondents generally have a positive perception of other members in the group due to the group's ability to provide informative and engaging posts for its members."--Author
Thesis
Keywords: Online social networks; Social media -- Case studies; Asians -- Race identity; Race identity -- Social aspects; Ethnicity -- Asia; Southeast Asia